Monitoring invasive alien macroinvertebrate species with environmental DNA. (3rd February 2022) - Blackman, Rosetta C.; Brantschen, Jeanine; Walser, Jean‐Claude; Wüthrich, Remo; Altermatt, Florian
Abstract: Regular monitoring of ecosystems can be used for the early detection of invasive alien species (IAS), and provide information for management and preventing them from becoming established or advancing into new areas. Current methods of monitoring freshwater systems for IAS can be both financially costly and time‐consuming, with routine monitoring often carried out at low intensity and at only a small number of sites. In this study, we evaluate how environmental DNA (eDNA) metabarcoding for monitoring freshwater macroinvertebrate IAS compares to traditional kick‐net sampling as part of a national (Switzerland) and a catchment monitoring programme. Kick‐net sampling was more fruitful for the detection of several well‐known target macroinvertebrate IAS. However, eDNA samples proved complementary for the detection of IAS that belong to species often being unnoticed by traditional sampling due to methodological or taxonomic reasons. Specifically, the invasive jellyfish Craspedacusta sowerbii, hardly detectable using classic kick‐net sampling, was found to be widespread in both the national and the catchment‐scale monitoring with the eDNA method only. Our study shows that IAS detection using eDNA is easily implemented in both national‐ and catchment‐scale monitoring campaigns. However, successful detection of target IAS is still highly dependent on primer choice, species' biology, and availability of adequate markers. Specifically, multiple markers should be considered for detecting IAS from several different taxonomic groups, such as those under the 'freshwater macroinvertebrate' umbrella term. While eDNA is still developing in terms of these fundamental methodological requirements, surveillance for both target and non‐target IAS using eDNA is likely to increase efficiency in early detection of IAS in freshwater systems.